Relation between vulva color and reproductive performance in rabbits using AI technique - Abdel-Ghaffar A.E.; Agag M.A. (Rabbit production in hot climates, 1994)
A total number of 307 female New Zealand White rabbits were used to study the relationship between the color of the vulva and the reproductive performance using artificial insemination technique (AI), the conception rate (CR), pregnancy rate (PR) and litter size (LS) were recorded. Four groups were classified according to the vulva color: congested red, pink, purple and pale. Highly significant variations were recorded between the four groups in all parameters studied. The highest CR, shortest PD and largest LS were recorded for the congested red group. The pale vulva group failed to conceive.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)